IN VITRO PROPAGATION FOR BIOCONSERVATION OF THREATENED BRASTAGI CITRUS IN NORTH SUMATRA INDONESIA - ISNAINI NURWAHYUNI,; RIYANTO SINAGA, (International Journal of Pharma and Bio Sciences, 2014)
In vitro propagation for bioconservation of threatened Brastagi citrus, local citrus in North Sumatra Indonesia is explained. The aims of bioconservation is to protect Brastagi citrus from diminish in the ecosystem due to the eruption of Mount Sinabung. The studies were conducted through cuting bud propagation to prepare explant sources followed by in vitro propagation to obtain plant seedling. The propagation was carried out by cutting the bud from branch of survive Brastagi citrus and stick onto the bark of sour citrus (Citrus aurantium) root stock. In vitro propagation was conducted experimentally with treatment combinations to obtain seedling of Brastagi citrus for bioconservation. The results showed that cutting bud propagation has successfully conducted to rescue three varieties of Brastagi citrus and to provide explant material for in vitro propagation. The callus were grown in all explants for all treatments. Two types of callus were observed, one in brown color, watery and non embryogenic, and the other was embryogenic callus with green color. The embryogenic callus is nodular that was develops and directly regenerate to plantlet. Growth stimulator in medium culture was significantly influenced callus induction, the growth of somatic embryo, plantlets, leaves, and roots.